CT findings of Talaromyces marneffei infection among HIV patients with lymphadenopathy - Zhu, Xiao-ling; Tang, Guang-Xiao; Liu, Xue-yan; Li, Ran; Lv, Sheng-xiu; Wang, Guang-xian (Frontiers in Medicine, 2022)
Background: Talaromyces marneffei (T. marneffei) is an opportunistic fungal pathogen commonly found in human immunodeficiency virus (HIV) patients that often infects lymph nodes. Knowledge about the computed tomography (CT) characteristics of T. marneffei lymphadenopathy in HIV patients is limited. The aim of this study was to investigate the clinical and CT characteristics of T. marneffei lymphadenopathy to improve its diagnosis and promote recognition of this type of infection in radiology. Methods: Between February 2019 and June 2021, we retrospectively reviewed the clinical features and CT characteristics of T. marneffei lymphadenopathy in 21 HIV patients. Results: The clinical symptoms of T. marneffei infection are nonspecific. Anemia (100%), fever (85.7%) and cough and sputum production (76.2%) were the most frequent symptoms. Multiple lymphadenopathies, mainly in the mediastinum (76.2%) and mesentery (82.4%), can be fused (14.3%) and necrotic (52.4%), with slight (41.7%) and moderate enhancement (58.3%) that is heterogeneous. In addition to involving the lymph nodes, the lesions involved the lungs (81.0%), liver and spleen (42.9%), and small intestine (14.3%). Conclusions: T. marneffei is prone to affecting lymph nodes and extranodal organs in HIV patients. Although the clinical manifestations of T. marneffei infection are not specific, the possibility of T. marneffei infection should be considered if CT findings indicate multiple lesion sites.